RURAL WOMEN'S ATTITUDE AND INVOLVEMENT IN POST-HARVEST PROCESSING OF VEGETABLES - M. H. Kabir; S. Afroz; M. M. Alam; M. S. Rahman (Journal of Animal and Plant Sciences, 2023)
Traditionally women are mostly engaged in household-based income generating activities. Post-harvest processing of vegetables has recently gained much attention due to its value addition utilities. Therefore, in this study, we tried to understand women farmers’ attitudes towards and involvement in, post-harvest processing of vegetables. Data were collected through face-to-face interviews using a pre-tested questionnaire from 212 respondents in Dhaka district of Bangladesh. The data were interpreted with descriptive statistics, multivariate regression analysis and a logit model. About 71% of rural women had a favorable attitude towards post-harvest processing; 43% of them were involved in the post-harvest processing of vegetables. Women's attitude towards post-harvest processing of vegetables was influenced by age, education, household size, and their frequency to travel outside of their social system. Their involvement in post-harvest processing of vegetables was affected by education, group membership, media contact and time spent in home management. ‘Gender disparity in earnings’ was the most severe barrier to expanding women's involvement in vegetable processing, followed by ‘lack of land ownership status’, ‘spouse dominance’ and ‘social norms and tradition’. Motivating women in income-generating activities and introducing advanced yet low-cost and less-labour intensive technologies would enable them to participate in the post-harvest processing of vegetables.
Keywords: agriculture; attitude; constraints; gender; logit model